2011
DOI: 10.1136/bjo.2010.191726
|View full text |Cite
|
Sign up to set email alerts
|

Smooth pursuit in infants: maturation and the influence of stimulation

Abstract: SPEM show an intensive maturation between 2 and 6 months of life. By 6 months of age SPEM have already reached an almost adult-like gain of 0.8 or higher. Further maturation is slow and still incomplete by the age of 18 months. Stimulus velocity and size have an important impact on the smooth pursuit quality, which should be considered in smooth pursuit testing in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…The large improvement in smooth pursuit performance on the 9 degree-per-second task between four and six months of age suggests rapid development of these brain regions over that time span. However, in contrast to previous work suggesting that the development of brain areas controlling SPEM is fairly mature by six months of age [24,28], the lack of an age effect and the finding that overall performance remains far below adult levels, even for six-month-olds, suggest that additional maturation of these brain regions remains.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The large improvement in smooth pursuit performance on the 9 degree-per-second task between four and six months of age suggests rapid development of these brain regions over that time span. However, in contrast to previous work suggesting that the development of brain areas controlling SPEM is fairly mature by six months of age [24,28], the lack of an age effect and the finding that overall performance remains far below adult levels, even for six-month-olds, suggest that additional maturation of these brain regions remains.…”
Section: Discussioncontrasting
confidence: 99%
“…Three established infant SPEM measures were assessed: (a) the percentage of time spent in smooth pursuit (calculated by dividing the time spent in smooth pursuit by the total artifact-free time including both smooth pursuit and saccades; (b) the frequency of forward saccades (number per second of artifact free recording); and (c) the longest duration of uninterrupted smooth pursuit the child was able to generate [24,2830]. Figure 1 shows a sample tracing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean velocity of smooth pursuit was therefore 3.5°–15°/s, although maxima of smooth pursuit gains of 1–1.2 were observed (7.5–45°/s) [9]. In a study of smooth pursuit on healthy full-term newborns, eye movement velocities were found below 15°/s, and, most often, even below 10°/s [10].…”
Section: Discussionmentioning
confidence: 91%
“…All the investigated risk factors might affect the rapid phase of brain development or induce structural damage by inflammation, hypovolemia, hypotension, hypoxia, hypercarbia, and inadequate nutrition and growth. These different pathogenic factors might, within the frame of this study, affect the rapid and vulnerable development of the visual cortical pathways (1,4–8). Development of SP is dependent on intact visual pathways in the brain, both the subcortical pathways – the major visual pathways for motion stimuli during the infant’s first 6–8 weeks – and the primary visual cortical pathways that become the major visual pathways after 6–8 weeks and develop rapidly during early infancy (1,29).…”
Section: Discussionmentioning
confidence: 99%